Penerapan Biophilic Design pada Bangunan Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak Kota Bekasi - Maharani Hanna Shafiyya; Pancawati Dewi (ATRIUM: Jurnal Arsitektur, 2021)
Title: Application of Biophilic Design in Regional Technical Implementation Unit for the Protection of Women and Children of Bekasi City   Based on data from the National Commission for Women and Children in 2019, Bekasi City occupies the second position in the number of cases of violence against women and children after Jakarta. The response that has been done by the Bekasi City Government is to establish the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) which provides services and psychological recovery for victims. Regarding psychological recovery, researchers agreed that nature plays a major role in the human psychological recovery process. So the design concept of this building is restoration through nature by incorporating natural features in the form of green space into the building. In designing the method applied is through the Biophilic Design approach with 14 Patterns of Biophilic Design as a guide in designing. The results of the research are the application of biophilic design patterns to the landscape, exterior, and interior buildings.